2009
DOI: 10.1038/aps.2009.125
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of albumin nanospheres loaded with gemcitabine and their cytotoxicity against BXPC-3 cells in vitro

Abstract: Aim: To optimize formulation methods for loading gemcitabine (GEM), the main drug against pancreatic cancer, into albumin nanoparticles for extended blood circulation and improved efficacy. Methods: GEM was loaded into two sizes of disolvation-crosslinked bovine serum albumin nanoparticles, with a mean diameter of 109.7 nm and 405.6 nm, respectively, by co-precipitation (the direct method) and follow-up adsorption (the indirect method). The antitumor activities of the two nanoparticulate formulations, were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…This is attributed by the higher phagocytotic rates for the uptake of nanoparticles in liver and spleen, than cells of other tissues. A similar phenomenon was observed in the selective targeting of albumin nanospheres (Li et al, 2009). The results of stability testing revealed that there was no significant change in the mean Figure 2.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This is attributed by the higher phagocytotic rates for the uptake of nanoparticles in liver and spleen, than cells of other tissues. A similar phenomenon was observed in the selective targeting of albumin nanospheres (Li et al, 2009). The results of stability testing revealed that there was no significant change in the mean Figure 2.…”
Section: Discussionmentioning
confidence: 52%
“…Gemcitabine represents an advance in pancreatic cancer care. The major limitation of gemcitabine is short half life and strong side effects when administered intravenously (Li et al, 2009;Jia et al, 2010). Short half lives are commonly due to fast renal clearance, decreased protein binding and enzymatic degradation (Werle & Bemkop Schnurch, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The albumin nanoparticles were prepared by the desolvation-crosslinking technique as previously described. 26 Briefly, 10 ml aqueous BSA (2.5% w/v) was prepared. The pH was adjusted to 8.0-8.2 with NaOH (1 mol/L).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported on the use of albumin nanoparticles as drug carriers to encapsulate Gem in pancreatic cancer, [26][27][28] in which two sizes of Gem-loaded albumin nanoparticles (110 nm and 406 nm) were successfully prepared. Both indicated improved antitumor cytotoxicity and prolonged drug release characteristics.…”
Section: Introductionmentioning
confidence: 99%